The RESEARCH ANALYSIS OF TRANSFORMATION NEW ASSORTMENT DEVELOPMENT: RESEARCH ANALYSIS OF TRANSFORMATION NEW ASSORTMENT DEVELOPMENT - O'g'iloy, Turdiyeva; Khojiyev , Abdurakhim (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective.The purpose of this scientific research is to develop dynamic, convenient, and bright models of dynamic, convenient, and dynamic assortments based on the analysis and analysis of the creative and transformational assortments of designers from different countries. Methods. In the research, products that change their changing and transformational form, clothes, creativity of designers of different countries, scientific researches are analytically studied. Results. Conclusions were made based on the analysis of the sources, and a new range of dynamic, convenient, bright models of the transformational, shape-changing range were developed. Conclusion. In conclusion, it can be said that various products and clothes made in the form of change and transformation have become one of the current directions of creativity of designers of different countries. In this article, a transformational new assortment design was developed based on the literature review. Key words: Transformational, changing, assortment, invention, useful model, convenient, functional, harmonious, modern, needs.